Spatial Modelling Habitat Suitability of Javan Langur (Trachypithecus auratus É. Geoffroy Saint-Hilaire, 1812) in Bromo Tengger Semeru National Park (TNBTS), East Java - Ningtyas, Ari Nadya; Aryanti, Nirmala Ayu; Susilo, Tander Scila Serata Dwi; Rahmadana, Mahmuddin; Agustin, Ika Yuni (Journal of Tropical Biodiversity and Biotechnology, 2024)
Javan Langur (T. auratus) is well-known as one of endemic primates from Java, Bali and Lombok Islands. The activities of land clearing, vegetation conversing, wild hunting and illegal wildlife trading are the main causes of the extinction of the Javan Langur. It can be used as an important issue for conservation action by making prediction maps of suitable habitat potential, especially for species facing a high risk of extinction in the wild.  We were documenting an information about potential habitat for Javan langur using spatial suitability model in order to provide rigorous information as the basis for conservation activities of Javan langur in TNBTS. We used Landsat-8 TM image and geospatial data to support analysis as a representative of environmental parameters in order to develop the habitat model. We were using maximum entropy (MaxEnt) algorithm refers to Javan langur presence or absence. The results showed that the suitability of the Javan langur habitat in TNBTS has an excellent model accuracy level with an AUC (Area Under the Receiver Operating Characteristics) value of 0.964 and a standard deviation of 0.961. Parameters with the highest response values here are elevation, NDVI (Normalised Difference Vegetation Index) and temperatures.